Совершенствование инструмента с учётом особенностей бурения различными способами - Линенко-Мельников, Ю.П.; Агеева, И.Ю. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
In the article the special features of the main methods of slits and boreholes drilling in the
mountain rocks of different strengths with the hard–alloy and artificial diamond instrument are shown.
The process of instrument wearing out during rotary drilling with strokes is examined, as
well as the cases of implementing of hard–alloys elements with supporting of implementing of
hard–alloys elements with supporting of their self–rotating.
The advantages and disadvantages of each of above – mentioned methods of drilling are
shown as well as the ways of the further improvement for each method.